Development of determination method and study of piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio) acetate in milk of cows in 12 hours after administration - B. O. Varynskyi; Ye. O. Karpun; V. V. Parchenko; O. I. Panasenko; B. P. Kyrychko; І. V. Hyrenko (Zaporozhye State Medical University, 2019)
The purpose of our work was developing the HPLC-MS method for determining piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio) acetate and researching the presence of residual amounts of piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio) acetate in cow's milk in 12 hours after injection. Materials and methods. Agilent 1260 Infinity Liquid Chromatography System (degasser, binary pump, autosampler, column thermostat, diode array detector, single quadrupole mass spectrometer Agilent 6120. Results. The method of determination of piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio) acetate in cow's milk was developed and the residual amounts of piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio) acetate in cow's milk in 12 hours after injection was determined. Conclusions. The conditions for sample preparation of milk samples for the determination of piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio)acetate have been proposed. It was found that 0.5 % methanoic acid is the most favorable protein precipitation agent. The content of the medicinal substance in the cow's milk sample was measured in 12 hours after the injection of the 1 % solution.